Relationship between mother’s knowledge and behaviour with oral health status of early childhood - Abdat, Munifah; Ramayana, Ivan (Universitas Padjadjaran, 2020)
Introduction: Early childhood period has a high caries risk that needs special attention from parents, especially the mothers, as their role models. Mothers’ knowledge and positive behaviour towards oral health care are essential in preventive dentistry since it is the crucial thing that can support the children’s oral hygiene. Purpose of study was aimed to analyse the relationship between the mother’s knowledge and behaviour regarding oral health with the early childhood oral health status. Methods: Type of study was a cross-sectional study with correlational research method. The material from this research were questionnaires and standard instruments for an oral examination. The study was conducted on 44 children of the early childhood period and their mothers, which was chosen as sample using a purposive sampling technique for respondents who met the inclusion criteria. The inclusion criteria were mothers who took up their children to the mother and children’s health centre, children in the early childhood period with complete deciduous teeth eruption, and willing to participate in the research. A Kendall’s-tau test was used for statistical analysis. Results: The results showed that the def-t index was 7.6 (very high) and there was a significant relationship between mother’s knowledge (p-value=0.0001) and behaviour (p-value=0.004) towards oral health status of the children (def-t index). The results also showed strong correlation coefficient to knowledge (τ = -0.643) and sufficient correlation coefficient to behaviour (τ = -0.415). Ironically, mothers with sufficient knowledge regarding the children’s oral health are not fully reflected in daily oral hygiene practice. The mean value of caries teeth in each child was seven teeth, mostly found in children with mothers with poor oral health knowledge and behaviour. Conclusion: There is a strong relationship between mother’s knowledge and oral health status of early childhood, while the mother’s behaviour and oral health status has a moderate relationship.